Los pueblos indígenas y la ciudadanía en México - Peredo Ibarra, Carlos Manuel (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
The present work shows a long-range historical journey that goes deeper not only into the ways indigenous groups of people in Mexico have gained citizenship rights; but also, how they have exercised them along the national history. Having analyzed such ways, we will see that the exercise of their citizenship rights is far away from the ideal conception of 'citizen', conceived by the Mexican state. On the other hand, it is going to be seen that in many cases those ways have been an answer to the interest of their own communities in order to maintain their fragile autonomy from the Mexican state, in an effort to preserve their own forms of organization, culture and identity.

El presente trabajo ofrece un recorrido histórico de largo alcance que ahonda en las formas en que los Pueblos Indígenas de México han accedido a la ciudadanía y cómo la han ejercido a lo largo de la historia nacional. Analizaremos cómo las formas en que los indígenas mexicanos han ejercido la ciudadanía no siempre corresponden con el ideal ciudadano construido desde el Estado, sino que en muchos casos han respondido al interés de las comunidades por mantenerse relativamente autónomas frente al Estado, conservando sus propias formas de organización y culturas.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2020-0712; Ciudadanía; Indígenas; Estado; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2873